Influence of dihydropyrimidine dehydrogenase gene (DPYD) coding sequence variants on the development of fluoropyrimidine-related toxicity in patients with high-grade toxicity and patients with excellent tolerance of fluoropyrimidine-based chemotherapy - Kleibl, Z; Fidlerova, J; Kleiblova, P; Kormunda, S; Bilek, M; Bouskova, K; Sevcik, J; Novotny, J (Neoplasma, 2009)
Alterations in dihydropyrimidine dehydrogenase gene (DPYD) coding for the key enzyme (DPD) of fluoropyrimidines (FPs) catabolism contribute to the development of serious FPs-related toxicity. We performed mutation analysis of DPYD based on cDNA sequencing in 76 predominantly colorectal cancer patients treated by FPs with early development of high (grade 3-4) hematological and/or gastrointestinal toxicity. Six previously described [85T>C (C29R), 496A>G (M166V), 775A>G (K259E), 1601G>A (S534N), 1627A>G (I543V), IVS14+1G>A, 2194G>A (V732I)] and two novel [187A>G (K63E) and 1050 G>A (R357H)] non-synonymous DPYD variants were found in 56/76 (73.7%) high-toxicity patients. Subsequently, these alterations were analyzed in 48 patients with excellent long-term tolerance of FPs and in 243 controls and were detected in 37/48 (77.1%) and 166/243 (68.3%) cases, respectively. Analysis of these alterations as risk factors for development of toxicity in pooled FPs-treated population demonstrated that C29R negatively correlated with overall gastrointestinal toxicity (OR = 0.48; 95%CI 0.23-1.0) and M166V in women protected against overall hematological toxicity and neutropenia (both OR = 0.26; 95%CI 0.07-0.89), whereas IVS14+1G>A (found in five high-toxicity patients only) increased risk of mucositis in overall population (OR = 7.0; 95%CI 1.1-44.53), and thrombocytopenia in women (OR = 10.8; 95%CI 1.24-93.98). Moreover, we identified a strong association of V732I with leucopenia (OR = 8.17; 95%CI 2.44 - 27.31) and neutropenia (OR=2.78; 95% CI 1.03-7.51). Our data enabled characterization of "high risk" haplotypes (carriers of IVS14+1G>A or V732 lacking M166V) representing small (22% female and 11% male patients), population in high risk of serious hematological toxicity development, and in patients with "lower risk" that unlikely develop serious hematological toxicity [carriers of M166V without IVS14+1G>A and V732I in females (32% women), and non-carriers of C29R, M166V, IVS14+1G>A, and V732I in males (46% men)]. Our results indicate that genotyping of several DPYD variants may lead to stratification of patients with respect to the risk of serious hematological toxicity development during FPs treatment.
Keywords: senioři; Immunoenzyme Techniques; Capecitabine; Disease Progression; hematologické nádory; kolorektální nádory; Open Reading Frames; Retrospective Studies; progrese nemoci; Prognosis; fluoruracil; polymerázová řetězová reakce; výsledek terapie; Fluorouracil; Deoxycytidine; Polymerase Chain Reaction; capecitabinum; Hematologic Neoplasms; Colorectal Neoplasms; mužské pohlaví; Middle Aged; mutace; genetická variace; míra přežití; Adult; Dihydrouracil Dehydrogenase (NADP); Genetic Variation; chemorezistence; Neoplasm Staging; imunoenzymatické techniky; ženské pohlaví; prognóza; Mutation; dihydrouracildehydrogenasa (NADP); retrospektivní studie; Drug Resistance, Neoplasm; deoxycytidin; Humans; Survival Rate; otevřené čtecí rámce; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; staging nádorů; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; Treatment Outcome; lidé; Male